PERILAKU KOMUNIKASI MAHASISWA DI MESSENGER APPLICATION - Wida, Estika (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTThe presence of messenger application makes communication between lecturers and students easier, but in fact the ease gives negative impact so that the ethics should be owned by the students have decreased. At the time of contacting the lecturers, some of them did not say hello, introduced themselves, used informal language and were pushy. The purpose of this research is to know the student communication behavior in messenger application. Theory used is Theory of Communication Competence, Management of Anxiety and Uncertainty Theory and Computer Mediated Communication Theory. The research method is qualitative using case study data analysis. The results of this research that communicating with the lecturer using an informal language, calling a lecturer, not introducing himself, no apology does not mean the student is not polite. Familiarity, self-disclosure, and the environment shared between lecturers and students influence communication behavior. Students who have intimacy and openness communicate in a relaxed manner, but unlike students who lack familiarity and openness with the lecturers so that they communicate rigidly and reluctantly. Students decided to using whatsapp because is more effective and more personal. Communication competencies held by students are at the conscious competence stage, where students realize that they are able to understand, maintain and overcome how to communicate with lecturers. Students overcome their concerns before contacting lecturers using anxiety reduction and uncertainty strategies, 1) Passive strategy (students observing lecturers’ behavior when communicating in class), 2) Active Strategy (students ask senior lecturers), and 3) Interactive Strategy (students ask directly to the lecturer about the character of the lecturer).Keywords : Communication behavior, student, messenger application, lecturers.